Risk factors for cardiovascular diseases in rural residents of the Altai Krai: data from the ESSE-RF study - A. V. Aleksentseva (Российский кардиологический журнал, 2021)
Aim. To study the prevalence of behavioral and biological risk factors for noncommunicable diseases among rural residents of the Altai Krai.Material and methods. The object is a sample of male and female population obtained during the ESSE-RF study. The survey was conducted using a standard questionnaire. We assessed the level of blood pressure (BP), total cholesterol, height, weight of the respondents. The study involved 765 people living in rural areas aged 25-64 years, 35,4% of whom were men (n=271) and 64,6% — women (n=494). The mean age was 44,8±11,6 and 45,6±11,8, respectively.Results. The prevalence of hypertension was 40,3% (men, 42,1%; women, 39,4%). In addition, 77,6% of the respondents were informed about their blood pressure. With age, the incidence of elevated blood pressure increases, from 13,8% at 25-34 years to 64% in the 55-64 age group. Obesity was revealed in 34,2% of the population (men, 22,4%; women, 44,9%). Hypercholesterolemia occurs in 56,2% (men, 45,9%; women, 62,4%). The prevalence of diabetes was 4,3% (men, 2,2%; women, 5,7%). The prevalence of smoking in the sample was 24,1% (men, 50,9%; women, 9,6%). Excessive salt intake was found in 60,4%, insufficient consumption of vegetables and fruits — in 62,1% of respondents.Conclusion. The study made it possible to assess the prevalence of risk factors for chronic noncommunicable diseases in rural residents of the Altai Krai. Analysis shows that smoking dominates in men, while obesity and hypercholesterolemia — in women. Among the representatives of both sexes, a high rate of low physical activity and poor nutrition was noted. The data obtained determines the need and priorities for preventive measures to increase the motivation of residents to follow a healthy lifestyle.